Adult Bochdalek hernia following living donor left hepatectomy repaired by thoracoscopy‐assisted surgery: A case report. Issue 1 (26th August 2021) - Takagi, Kosei; Kuise, Takashi; Yoshida, Kazuhiro; Yoshida, Ryuichi; Umeda, Yuzo; Fujiwara, Toshiyoshi; Yagi, Takahito
Abstract: Bochdalek hernia is a congenital diaphragmatic hernia (DH). Herein, we report a case of adult Bochdalek hernia following living donor hepatectomy repaired by thoracoscopy‐assisted surgery. A 36‐year‐old man underwent living donor left hepatectomy. Four months later, the patient presented with acute epigastric pain. Computed tomography found the left‐sided DH in which the stomach was incarcerated into the pleural cavity without ischemic changes. As endoscopic intervention was unsuccessful, the herniated stomach was repositioned by thoracoscopy‐assisted surgery. The 3‐cm hernia orifice was found to have a smooth edge with no hernia sac, suggesting Bochdalek hernia, and the defect was primarily closed. The patient was followed up for 20 months without hernia recurrence. This is the first presentation of a case of Bochdalek hernia following donor hepatectomy. In cases of early detected DH, primary repair via a transthoracic approach with thoracoscopy‐assisted surgery is safe and feasible.